Metal Nanoparticles with Liquid‐Crystalline Ligands: Controlling Nanoparticle Superlattice Structure and Properties. Issue 7 (30th April 2014) - Lewandowski, Wiktor; Wójcik, Michał; Górecka, Ewa
Abstract Nanoparticle ordered aggregates are promising candidates for future application in a variety of sensing, optical and electronic technologies, mainly based on collective interactions between individual nano‐building blocks. Physicochemical properties of such assemblies depend on nanoparticle spacing, therefore a lot of effort throughout the last years was put on development of assembly methods allowing control over aggregates structure. In this minireview we describe efficient self‐assembly process based on the utilization of liquid‐crystalline ligands grafted onto nanoparticle surface. We show strategies used to synthesize liquid‐crystalline nanoparticles as well as discuss parameters influencing structural and thermal characteristic of aggregates. It is also demonstrated that the liquid‐crystalline approach offers access to dynamic self‐assembly and metamaterials with anisotropic plasmonic properties, which makes this strategy unique among others.